2018
DOI: 10.3892/etm.2018.6154
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic manifestation of Wegener's granulomatosis: Computed tomography findings and analysis of misdiagnosis

Abstract: The aim of the present study was to investigate the computed tomography (CT) manifestations of Wegener granulomatosis (WG) in the chest and potential reasons for misdiagnosis. Conventional CT scans and clinical data of 45 patients with WG were retrospectively analyzed. Patients typically presented with multiple system involvement, primarily in the upper and lower respiratory tract. The incidence of thoracic involvement was 75.56% (34/45). Radiographic features were varied between cases in the present study, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…In the current study, it was shown that increased thickness of the paranasal sinuses, pulmonary cavity, and pulmonary nodules are the most common radiological findings in GPA patients. Consistent with these results, Jiakai Li et al, in a study of 45 GPA patients, showed that cavitation was the most common radiological finding in those patients [11]. A recent study of 225 GPA cases showed that the presence of solid and pulmonary cavity nodules was associated with poorer prognosis in those patients [12].…”
Section: Discussion_____________________________mentioning
confidence: 63%
“…In the current study, it was shown that increased thickness of the paranasal sinuses, pulmonary cavity, and pulmonary nodules are the most common radiological findings in GPA patients. Consistent with these results, Jiakai Li et al, in a study of 45 GPA patients, showed that cavitation was the most common radiological finding in those patients [11]. A recent study of 225 GPA cases showed that the presence of solid and pulmonary cavity nodules was associated with poorer prognosis in those patients [12].…”
Section: Discussion_____________________________mentioning
confidence: 63%
“…Hemoptysis is the most common but not specific clinical manifestation of DAH [10] was present in our case. The CT of pulmonary involvement in AAV was manifested with multiple nodules of variable size randomly distributed throughout the lungs, with airspace consolidation and ground-glass opacities, while in anti-GBM antibody disease was ground-glass and consolidated opacities that progress to a reticular "crazy paving" pattern over a few weeks [11]. In our case, the presence of nodules was more indicative of AAV, but their non-cavitation and radiographic resolution during follow-up were more in the direction of anti-GBM antibody disease.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of GPA can be made if (a) histologic results are compatible with the guidelines of the Chapel Hill Consensus Conference for GPA; (b) histologic results are compatible with microscopic polyangiitis, and the patient has surrogate markers of GPA; or (c) there are no histologic results, but there are positive surrogate markers and serologic results for antiprotease 3, myeloperoxidase, and antineutrophil cytoplasmic antibodies (ANCA). As with EGPA, CT is the mainstay in evaluating patients with GPA who have suspected thoracic involvement (17).…”
Section: Granulomatosis With Polyangiitismentioning
confidence: 99%
“…The incidence of thoracic involvement in GPA is up to 75% (17). Nodules or masses with or without central cavitation are the most frequent finding in GPA (Fig 5).…”
Section: Granulomatosis With Polyangiitismentioning
confidence: 99%